Socio-environmental Impacts Associated with Burning Alternative Fuels in Clinker Kilns - Mainier, F. B.; Monteiro, L. P. C.; Mainier, R. J. (Engineering, Technology & Applied Science Research, 2013)
The pollutants found in emissions from cement plants depend on the processes used and the operation of the clinker kilns. Another crucial aspect concerns the characteristics of raw materials and fuels. The intensive use of fuels in rotary kilns of cement plants and the increasing fuel diversification, including fuels derived from coal and oil, from a multitude of industrial waste and from biomass, charcoal and agricultural waste (sugarcane bagasse, rice husk), is increasing the possibilities of combinations or mixtures of different fuels, known as blends. Thus, there are socio-environmental impacts associated with the burning of alternative fuels in clinker kilns. In view of the growing trend of entrepreneurs who want to target the waste produced in their unit and of the owners of the cement plants who want to reduce their production costs by burning a waste with lower cost than conventional fuels, it is necessary to warn that a minimum level of environmental care should be followed regarding these decisions. It is necessary to monitor the points of emission from cement kilns and in the wider area influenced by the plant, in order to improve environmental quality. Laboratory studies of burning vulcanised rubber contaminated with arsenic simulate the burning of used tires in cement clinker kilns producing SO2 and As2O3.